PERLINDUNGAN HUKUM BAGI PENENUN PEREMPUAN MELALUI KEBIJAKAN AFIRMASI DARI PERSPEKTIF KEADILAN PANCASILA (Dialogia Iuridica, 2020)
Weaving is a choice of work for women who live in rural areas, not only providing economic benefits but also preserving Indonesia's cultural wealth. According to a government report, weaving crafts make a large contribution to state revenue in the creative economy sector. This condition is inversely proportional to the situation of women weavers in rural areas, because they have limited access to low-interest capital and marketing at fair prices. This study to describe the importance of protecting women weavers and to analyze the importance of the regulation of Pancasila justice-based affirmation policies to protect female weavers. This is a normative study using legal materials sourced from laws, legal theories and the results of previous research. Research findings, first weaving has high velue for community. The current challenge is that weavers in villages above 40 years old, while there is very little interest in young women to weave. Second female weavers in the village rely heavily on high-interest capital loans and deliberately created unfair markets. Even though the government has a low-interest KUR program, women weavers find it difficult to access KUR because they do not have assets as collateral. This situation must be placed within the framework of women's limited access to justice. Pancasila justice which prioritizes communal interests is the perspective used to photograph this situation. This research suggests the need for affirmative policy arrangements for protection of women weavers through Regional Regulations at the Provincial, District and Village levels.